Impact and Challenges of Centres for Education and Community Action in Cameroon’s North West Region - Amungwa, Fonteh Athanasius (Journal of Education and Research, 2018)
This paper examines the impact of community education and challenges facing Centres for Education and Community Action as a rural development strategy in Cameroon. The study was conducted in the North-West Region of Cameroon, employing field observations, semi-structured interviews with key informants using a convenient sampling technique and through elaborate review of documents. These research instruments were blended into what is termed triangulation and the data collected was analysed descriptively. The main focus of qualitative analysis is to understand the ways in which people act and the accounts that people give for their actions. This paper posits that extreme dependence on the provision of Western formal education cannot solve the problems of a rapidly changing society like Cameroon, which is facing a long-term economic crisis and persistent unemployment issues of graduates. Consequently, education should be redefined in the context of the prevailing economic crisis to make it responsive to the aspirations of rural communities. Findings showed that community education had contributed towards rural development immensely but has suffered many challenges due to neglect of the field in the policy agenda. This paper recommends the integration of community education with formal education to facilitate group and community betterment in particular and rural transformation in general.